Performance, gastrointestinal morphometry, carcass and non-carcass traits in sheep finished on diets containing canola (Brassica napus L.) - Mayara Mitiko Yoshiraha Carneiro; Rafael Henrique de Tonissi e Buschinelli de Goes; Mayara Andressa Sabedot; Jefferson Rodrigues Gandra; Andrea Maria de Araujo Gabriel; Raquel Tenório de Oliveira; Nayara Gonçalves da Silva; Douglas Gabriel Anschau (Acta Scientiarum. Animal Sciences, 2021)
The objective of this study was to evaluate performance, gastrointestinal morphometry, carcass, and non-carcass traits in lambs finished on different levels of canola grain in the diet. Twenty-seven Santa Ines lambs with an average initial weight of 19.33 ± 1.39 kg were given different levels of canola grain in the diet: 0, 8, and 16%. Weights and body condition scores were determined at the beginning, every 14 days and at the end of the experimental period. Animals were slaughtered to assess gastrointestinal morphometry, carcass and non-carcass traits. The statistical design used was completely randomized. The inclusion of canola grain showed a linear effect (0.723) for the width and height of ruminal papillae in the ventral region of the rumen. Intestinal villi and crypts showed a quadratic effect, with peaks of 0.62 µm and 0.43 µm, with the inclusion of 8 and 16%, respectively. When evaluating carcass traits, a decreasing linear effect was found for hot and cold carcass yield with 16% inclusion of canola. Canola grain can be used as an alternative in diets for finishing sheep up to 8% inclusion in the diet without affecting performance, ruminal and intestinal histometry, carcass, and non-carcass traits.